Have You Heard of MS? - Kantenwein, Krystin (Ars Medica, 2019)
Initially, I wrote this non-fiction essay as a way to cope with my undiagnosed neurological symptoms. However, as I continued writing, this story shifted and evolved into one that speaks directly to women and the doctors that dismiss them -- women who present with physical symptoms, but leave with a diagnosis of depression. Although mental illnesses can cause physical ailments, I seek to illuminate the assumptions doctors have made about my body and mind in hopes that women, not only those with neurological conditions but those who remain undiagnosed, can feel heard, when for so long we have been silenced.